Democracia e elitismo - Salles, Rubens César Guimarães (2017)
Theproposal of this work is todemonstrate, from ahistorical-conceptual analysis,the criticismdirected to the democracyin the period of itsemergence, or invention, inClassical Greeceand its relation with otherforms of government notablythearistocracy. From this analysiswe'lltryto understand the relationship between thatform of government and the Elites' theory, based on the assumption that democracyhasalways been, likeallotherforms of government, under the influenceof aminoritythat holds power andcommands the majority. Does the democracy, whether as awayofgoverningastateor of managingpoliticalorganisms, is, paraphrasingSartre,condemned to elitism?To this concept of elitism wecan't applyan immediate valuejudgment, sinceit has direct and similar connection with concepts worked bytraditionas Aristocracyand Oligarchythat areunderstood from Aristotlerespectivelyas afair and deviantform of government, thereforewith positivevalues, thefirst oneandnegativethe second one. Finally, wewillalso investigate two of the so-calleddemocraticelitists–Joseph SchumpetereRobert Dahl–whoseek not onlyareconciliation between the values of elitism and democracy, but, based on theirreading of the so-calledclassicalelitists–Gaetano Mosca, Vilfredo Pareto eRobert Michels–theycome to understand elitism as a condition of possibility for democracy.